Keterkaitan antara Halitosis dengan Bakteri Penyebab Periodontitis - Luki Astuti; Olivia Nauli Komala (Jurnal Kedokteran Gigi Terpadu, 2023)
Halitosis, often known as foul breath, refers to an unpleasant odor that emanates from the mouth cavity when inhaling or talking. Halitosis can have a negative impact on a person's quality of life, including symptoms of depression or anxiety, low self-esteem, embarrassment, prejudice, and social isolation. Bad breath can be caused by both intra oral and extra oral factors. Bacterial growth in the oral cavity is excellent for the production of volatile sulfur compounds (VSC). The posterior dorsum of the tongue, gingival sulcus, periodontal pockets, and gingival embrasures are all places where bacterias can accumulate. Fusobacterium nucleatum, Prevotella intermedia, Porphyromonas gingivalis, and Treponema dentiocola are known to actively produce VSC through interactions with specific substrates such as cysteine, methionine, tryptophan, arginine, and lysine to produce hydrogen sulfide (H2S) and methylmercaptan (CH3SCH3). However, the presence of VSC does not indicate the presence of periodontitis, as any space in the oral cavity that can cause the retention of bacteria/biofilms can become a site for bacterial decomposition, thereby facilitating the growth of VSC. Tongue cleansing is proven to help reduce the formation of VSC.